ADAPTING THE TREATMENT OF OVARIAN CYSTS ACCORDING TO THEIR TYPE IN DAIRY CATTLE - Silviu-Ionuț BORȘ; Alina BORȘ (Journal of Applied Life Sciences and Environment)
Ovarian cysts, estimated as the most frequent ovarian disorder in dairy cattle, can impact the economic aspect and trigger serious loss by affecting the reproductive performance. However, treatment strategies for ovarian cysts in dairy cattle are disputed, as some researchers favour the use of gonadotropin-releasing hormone (GnRH) for all cysts, whereas others recommend this treatment only for follicular cysts, with prostaglandin F2α (PGF2α) for luteal cysts, but not all of the dairy cattle responded to these regimes. Other studies mention a spontaneous recovery for some of the dairy cattle that present this disorder. However, the Ovsynch protocol appears to be the most used for treating ovarian follicular cysts, despite low pregnancy rates. Thus, this study’s main purpose is to assess by analogy the reproductive efficiency of multiparous dairy cattle with follicular cysts after treatment with a recommended dose of GnRH or a further Ovsynch protocol, and of cattle with luteal cysts after PGF2α or a further 12-day Presynch protocol, by comparing the reproductive responses between treated and non-treated cattle. It is remarkable that ten of the dairy cattle diagnosed with ovarian cysts recovered spontaneously without any hormonal intervention, but the reproductive performance indicates that treatment should be started as soon as the condition is diagnosed. Compared with other studies, our approach improved the conception (82.4% and 64.3%, respectively) and pregnancy rates (53.8% and 50%, respectively) in both follicular and luteal cysts.